Method of overloads' elimination on telecommunication networks - Gayvoronska, Galyna; Kryzanovska, Anna (Видавництво Львівської політехніки, 2012)
In this paper the decision of a problem of the overloaded switching node's unloading on telecommunication networks is given.
Keywords: Switching Node; Load; Overload; Unloading; Requirement